Implementasi Teologi Kerukunan Di Pura Labuhan Aji Kabupaten Buleleng - Heriyanti, Komang (Jayapangus Press, 2025)
Religious harmony in Indonesia is an important factor in maintaining national unity. This study attempts to describe the form of interfaith harmony at Labuhan Aji Temple, Buleleng Regency. The harmony between Hindus and Buddhists at Labuhan Aji Temple demonstrates that temples can be a place for interfaith practices through local traditions such as ngayah and the implementation of piodalan days. During piodalan days at Labuhan Aji Temple, not only Hindus carry out ngayah activities. But Buddhists also participate in ngayah preparing infrastructure for piodalan days. Thus, the purpose of this study is to provide an understanding that temples, as sacred places for Hinduism, have a space to unite communities of different faiths through the practice of local traditions. The method used in this study is a qualitative research method. Data were collected through observation, interviews, and document studies. Based on the data obtained, the results of this study are the implementation of the theology of harmony between Hindus and Buddhists at Labuhan Aji Temple, seen from the palinggih in the temple, some still use lanterns which are Buddhist ornaments and the standing of the Dwi Kwan Im statue. In addition, harmony can be seen on the piodalan day which starts from the ngayah process until during the piodalan, Buddhists wear Balinese traditional clothing and the same offerings as Hindus, such as banten.